Influence of Omeprazole on the Antiplatelet Action of Clopidogrel Associated With Aspirin - Gilard, Martine; Arnaud, Bertrand; Cornily, Jean-Christophe; Le Gal, Grégoire; Lacut, Karine; Le Calvez, Geneviève; Mansourati, Jacques; Mottier, Dominique; Abgrall, Jean-François; Boschat, Jacques (Journal of the American College of Cardiology, 2008)
Influence of Omeprazole on the Antiplatelet Action of Clopidogrel Associated With Aspirin: The Randomized, Double-Blind OCLA (Omeprazole CLopidogrel Aspirin) Study Martine Gilard, Bertrand Arnaud, Jean-Christophe Cornily, Grégoire Le Gal, Karine Lacut, Geneviève Le Calvez, Jacques Mansourati, Dominique Mottier, Jean-François Abgrall, Jacques Boschat In a previous observational study, we found the effect of clopidogrel as tested by vasodilator-stimulated phosphoprotein (VASP) phosphorylation to be diminished in patients receiving proton pump inhibitor treatment. In this double-blind placebo-controlled trial, 124 consecutive patients were randomized to receive either associated omeprazole (20 mg/day) or placebo for 7 days. The clopidogrel effect was tested on Day 1 and Day 7 in both groups by measuring platelet phosphorylated VASP. Our main end point was to compare platelet activation in the 2 groups. Omeprazole significantly decreased the antiplatelet effect of clopidogrel as assessed by a VASP phosphorylation test (p < 0.0001). This trial sought to assess the influence of omeprazole on clopidogrel efficacy. Clopidogrel has proved its benefit in the treatment of atherothrombotic diseases. In a previous observational study, we found clopidogrel activity on platelets, tested by vasodilator-stimulated phosphoprotein (VASP) phosphorylation, to be diminished in patients receiving proton pump inhibitor (PPI) treatment. In this double-blind placebo-controlled trial, all consecutive patients undergoing coronary artery stent implantation received aspirin (75 mg/day) and clopidogrel (loading dose, followed by 75 mg/day) and were randomized to receive either associated omeprazole (20 mg/day) or placebo for 7 days. Clopidogrel effect was tested on days 1 and 7 in both groups by measuring platelet phosphorylated-VASP expressed as a platelet reactivity index (PRI). Our main end point compared PRI value at the 7-day treatment period in the 2 groups. Data for 124 patients were analyzed. On day 1, mean PRI was 83.2% (standard deviation [SD] 5.6) and 83.9% (SD 4.6), respectively, in the placebo and omeprazole groups (p = NS), and on day 7, 39.8% (SD 15.4) and 51.4% (SD 16.4), respectively (p < 0.0001). Omeprazole significantly decreased clopidogrel inhibitory effect on platelet P2Y12 as assessed by VASP phosphorylation test. Aspirin-clopidogrel antiplatelet dual therapy is widely prescribed worldwide, with PPIs frequently associated to prevent gastrointestinal bleeding. The clinical impact of these results remains uncertain but merits further investigation. (OCLA: Influence of Omeprazole on the Antiplatelet Action of Clopidogrel Associated to Aspirin; http://www.clinicaltrials.gov/ct2/show/NCT00349661; NCT00349661)